The Correlation between Patient Load, Working Hours, and Tenure on Job Satisfaction Among Female Nurses in the Different Inpatient Wards of a Private Hospital in Jakarta: A Preliminary Study - Helenia Putri; Yohana Stefanie H. Samosir; Tiffany Rebecca; Innocentius Bernarto (Jurnal Ners, 2026)
In this business era, the hospital’s management must compromise between the human resources and the financial, especially for nurses. The management must analyse between the number of nurses, their workload, primarily their patient load and working hours to reduce turnover rate and higher job satisfaction that can improve their performance. Many studies try to explore these area but, for some variables is still contradictory, so this preliminary study try to see the correlation between patient load, working hours, and tenure on job satisfaction among female nurses in the different inpatient wards. This research employed a quantitative observational analytics with descriptive and associative approach, a cross sectional study. Among 29 female nurses who work in this private hospital in Jakarta, more than half of them have high job satisfaction, and there are no difference between different inpatient wards. The patient load and tenure did not have significant correlation with job satisfaction, but the working hours have significant correlation. Therefore, many other factors that have stronger correlation to the job satisfaction.